The burden of recurrent urinary tract infections in patients attending a tertiary care hospital in Northern India - Aishiya Ishrat; Shashi S Sharma; Saba Choudhary (Global Journal of Medicine and Public Health, 2024)
Background Recurrent urinary tract infections (UTIs) are primarily caused by reinfection by the same pathogen. The use of various antibiotics has been the mainstay in remodelling the rate of UTIs, but recurrent UTIs continue to affect people. The various antibiotics prescribed for the treatment of UTIs are imipenem, fosfomycin, ceftriaxone, quinolones, gentamicin, tetracycline, amikacin and nitrofurantoin. Studying the aetiology and antibiotic sensitivity pattern of uropathogens helps clinicians understand the resistance patterns among these microbes. Given the extensive economic and healthcare burden of UTIs and alarming antibiotic resistance, there is a crucial need to better understand the tendency of relapse and recurrence associated with UTIs. This study aims to assess the microbial aetiology and antibiotic sensitivity of isolates in UTIs, which may ultimately help clinicians formulate an empirical treatment.